Rancang Bangun Mesin Polishing untuk Proses Finishing Hairline pada Plat Stainless Steel - Azzam Bramasta; Moh. Miftachul Munir; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
As time goes by, the size of the company does not provide a guarantee in its development, but the agility and speed of the company are the keys. One of these competitions is in the polishing finishing process. Polishing finishing process is an industrial process that change the surface of amanufactured item to achieve certain properties. The machines used for the finishing process on stainless steel plates are not yet produced in the domestic market. In this study using the Ulrich method with an output of 3 machine design concepts that can produce a hairline finish on a stainlesssteel plate. The design and work drawings created using Autodesk Fusion 360 software. The list of requirements was obtained after an interview with one of the furniture industry parties was conducted. Then a selected design is determined in terms of functional, operational, safety, maintenance manufacturing, and price. The chosen concept is concept 2 which can adjust the height of the polishing roll with a 2 thread system. After being made, the machine can polish 3mm thick stainless steel 201 plate with a size of 1220 x 2440 mm in ± 25 minutes. The total budget required is Rp. 4,718,000, -.